Evaluasi Nilai Ekonomi Produk Shuttlecock (Studi Kasus:Home Industry Pembuatan Shuttlecock Merek LIYA Serengan Surakarta) - Ristanto, Ristanto, Ahmad Kholid Al Ghofari, ST. MT (2016)
The game of badminton is one sport familiar to the people of Surakarta, many badminton games or indirectly will trigger the growth of the manufacturing industry shuttlecock. One shuttlecock making industry in Surakarta is 'LIYA', the company in determining the cost of production is still using traditional methods, thus determining the cost of production is less accurate. Later the company also experienced problems due to rising raw material feathers often have great influence on the cost of production if there is an increase and uncertainty reservations. Furthermore, the products produced four variants that led to the break-even point determination or break event point becomes more complex. The purpose of this study was to determine the cost of production with activity based costing method, then a sensitivity analysis of raw materials and the level of demand shuttlecock feathers, the latter is to determine the breakeven point. The results of this study indicate that the use of the ABC method in determining the cost of production is cheaper than traditional methods, for quality shuttlecock 1 USD 37,016.80, quality 2 USD.37,010.94, then quality 3 USD 34,127.64 and quality 4 USD 29287.50. Furthermore, if there is an increase in raw material prices feathers by 10% and 20% still provide benefits for the company, and if it happens shuttlecock demand increase and decrease by 10%, 15%, and 20% still provide benefits for the company. Then to determine the break even point, the number of products that must be made are as many as 8932 slop. Keywords: activity aased costing, sensitivity analysis, the break even point